How the survey was held - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
In the October 2001 issue of Spore (number 95) and Esporo (number 45), a one-page article about the survey listed 10 open questions.These included questions on the reader's daily work, how many people read her or his Spore, preferred sections,...